Afghanistan EFL Teacher Preparation Institutions and EFL Teaching Efficacy in Public Schools - Nasim Danesh Tahsildar (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2019)
In Afghanistan university context, English Departments focusing on preparing or educating EFL teachers’ candidates are of two types; the Education Colleges’ English Departments (ECED) and the Literature Colleges’ English Departments (LCED). The purpose of this research is to investigate the extent to which the two EFL teacher preparation institutions in Afghanistan universities educate efficacious EFL teachers so as to teach English at public schools. It also aims at comparing the teaching efficacy level of male and female EFL teachers as the graduates of the two different English Departments (ECED and LCED) with different curricula in order to find out how these Departments educate public school EFL teachers. The study applied a survey questionnaire to obtain the data from 105 graduates of two English Departments as novice EFL teachers recruited by 45 public schools in a province in Afghanistan. The findings showed that both Departments educate highly efficacious EFL teachers. However, the level of efficacy between the two Departments is significantly different. The study also has some implications to schools of EFL teachers to comprehend their level of professional efficacy and certain implications to English Departments, Universities, and Afghanistan Ministry of Higher Education to understand how different English Departments’ graduates meet the public schools’ EFL requirements.